2018
DOI: 10.1590/1413-812320182311.23572016
|View full text |Cite
|
Sign up to set email alerts
|

Plantas medicinais e fitoterápicos na Atenção Primária em Saúde: percepção dos profissionais

Abstract: Resumo O Ministério da Saúde através da Política Nacional de Práticas Integrativas e Complementares (PNPIC) incentiva a oferta de Acupuntura, Homeopatia, Fitoterapia, Medicina Antroposófica e Termalismo no Sistema Único de Saúde (SUS). Este estudo avaliou o perfil de prescrição/sugestão e credibilidade no uso de plantas medicinais e fitoterápicos como terapia complementar entre 157 profissionais de 66 equipes da Estratégia Saúde da Família (ESF) do município de Blumenau. A coleta de dados foi realizada entre a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
75

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(121 citation statements)
references
References 20 publications
0
18
0
75
Order By: Relevance
“…Initially in the development of the proposal it was thought that the reduced number of indicative use of medicinal plants registered in the e-SUS could be related to the constraint that people could feel in confirming the use of medicinal plants, and the fear of losing access to industrialized medicine provided by SUS programs, or even fear of devaluation that many health care professionals can manifest in front of the knowledge about the use of medicinal plants due to a lack of knowledge and/or training. In a study by Mattos et al (2018), it was evaluated the prescription/suggestion and credibility in the use of medicinal plants in Blumenau/SC, in which were randomly selected health care professional in the UBS, and it was identified that 98.7% from the health care professionals agree with the initiative of the Ministry of Health, believe in the therapeutic effect of plants, but do not prescribe them for lack of knowledge.…”
Section: Resultsmentioning
confidence: 99%
“…Initially in the development of the proposal it was thought that the reduced number of indicative use of medicinal plants registered in the e-SUS could be related to the constraint that people could feel in confirming the use of medicinal plants, and the fear of losing access to industrialized medicine provided by SUS programs, or even fear of devaluation that many health care professionals can manifest in front of the knowledge about the use of medicinal plants due to a lack of knowledge and/or training. In a study by Mattos et al (2018), it was evaluated the prescription/suggestion and credibility in the use of medicinal plants in Blumenau/SC, in which were randomly selected health care professional in the UBS, and it was identified that 98.7% from the health care professionals agree with the initiative of the Ministry of Health, believe in the therapeutic effect of plants, but do not prescribe them for lack of knowledge.…”
Section: Resultsmentioning
confidence: 99%
“…O uso de plantas medicinais pela população, como método fitoterapêutico e preventivo, é um hábito pertencente à medicina antiga das mais diversas culturas, e que Development, v. 9, n. 9, e244997169, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i9.7169 atualmente ainda é praticado, principalmente nos países em desenvolvimento (Mattos et al, 2018). Os motivos para o emprego dessas espécies vegetais são o fácil acesso e o baixo custo, além dos indivíduos acreditarem que os produtos naturais são menos nocivos à saúde do que os medicamentos sintéticos (Silva & Santana, 2018;Menezes Filho & Castro, 2019a,b).…”
Section: Introductionunclassified
“…A partir disso, Estados e Municípios passaram a receber apoio técnico e financeiro para a ampliação das opções terapêuticas aos usuários, com garantia de acesso a plantas medicinais, fitoterápicos e serviços relacionados à fitoterapia, considerando o conhecimento tradicional de cada território. O Ministério da Saúde, por sua vez, passou a coordenar a gestão da Política, assim como as instituições que atuam na cadeia produtiva de plantas medicinais e fitoterápicos (MATTOS, et al, 2018;…”
Section: Introductionunclassified